2022
DOI: 10.1039/d1nj00098e
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent probe with a pyrazolo[4,3-c]quinoline core selectively recognizes c-MYC promoter G-quadruplexes

Abstract: An aptamer combined with a fluorophore could work as the fluorescent core of nucleic acid mimics of fluorescent proteins to locate and image functional biomolecules in cells. The locating precision...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…No nucleic acids have been reported to produce fluorophores or to be self-fluorescent . The fluorescence titration data suggested that Sor exhibited a weak fluorescence property.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No nucleic acids have been reported to produce fluorophores or to be self-fluorescent . The fluorescence titration data suggested that Sor exhibited a weak fluorescence property.…”
Section: Results and Discussionmentioning
confidence: 99%
“…No nucleic acids have been reported to produce fluorophores or to be self-fluorescent. 28 The fluorescence titration data suggested that Sor exhibited a weak fluorescence property. It was found that the fluorescence intensity of Sor decreased gradually with the addition of G4 in Figure 4D.…”
Section: Fluorescence Titrationsmentioning
confidence: 99%
“…20 The quinoline core has gained much attention in the designing of new fluorescent probes as it exhibits a strong binding capability with metal ions and excellent fluorescent properties. [21][22][23] Various quinoline containing probes are reported in the literature 21,24,25 for a variety of applications; 26 taking this into consideration, we chose the quinoline nucleus as the luminescent core and incorporated the ESIPT phenomenon in it for the detection of Cu(II) ions (Fig. 1b) and it is designated as "QHS".…”
Section: Introductionmentioning
confidence: 99%